Integrasi Regional Eropa Pasca Krisis Pengungsi 2015: Peran Area Schengen dalam Rekonstruksi Identitas Eropa melalui ‘Spatial “Othering”’ - Tara Kukuh Wardhani (Jurnal Hubungan Internasional, 2019)
This paper departs from the debate on the relevance of functional and neofunctionalmotives, such as economics, politics, and mobility, to the EU to maintainthe procurement of the Schengen area in the aftermath of insecurity crisiscaused by the large influx of refugees in 2015. This issue is important becausethe Schengen area has been one of the drivers of European regional integration.Thus, a more thorough analysis is needed in order to clarify other motives underlyingthe EU’s decision to maintain the procurement of the Schengen Area.Consequently, the author’s analysis yields three major findings to review motivesregarding the issue. First, the author analyses the transition of Schengen’s ‘ordering’forms in the European integration process, from functional to identity-drivenmotives. Second, the author analyses the ‘bordering’ practices undertaken by theEU through the Schengen area as an attempt to deconstruct the European rigidgeographical identity into a spatial geopolitical identity thus reinforcing exclusionof countries non-European. Third, the author analyses the possibility of increasingdegrees of EU inclusiveness as a strategic response to the Schengen crisis.